2007
DOI: 10.1002/jcb.21625
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of mitochondrial DNA copy number and expression are essential for preservation of mitochondrial function and cell growth

Abstract: To examine whether a reduction in the mtDNA level will compromise mitochondrial biogenesis and mitochondrial function, we created a cell model with depleted mtDNA. Stable transfection of small interfering (si)RNA of mitochondrial transcription factor A (Tfam) was used to interfere with Tfam gene expression. Selected stable clones showed 60-95% reduction in Tfam gene expression and 50-90% reduction in cytochrome b (Cyt b) gene expression. Tfam gene knockdown clones also showed decreased mtDNA-encoded cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 42 publications
7
108
1
8
Order By: Relevance
“…HeLa clones stably expressing shRNA targeting PNC1 exhibited a 40% and 60% reduction in protein did not show reduced proliferation (Figure 6b). Previous studies of mtDNA suppression after ethidium bromide treatment or suppression of critical components of the mtDNA maintenance machinery have shown impaired proliferation only when a critical level of mtDNA (less than 25% of initial content) is reached, which suggests that a minimal level of mtDNA is sufficient for cell proliferation (Jazayeri et al, 2003;Jeng et al, 2008). Interestingly, the effects of PNC1 on cell size and ROS production were not as tightly correlated with the degree of PNC1 suppression (Floyd et al, 2007 and this study).…”
Section: Pnc1 Regulates Mitochondrial Function and Emtmentioning
confidence: 99%
“…HeLa clones stably expressing shRNA targeting PNC1 exhibited a 40% and 60% reduction in protein did not show reduced proliferation (Figure 6b). Previous studies of mtDNA suppression after ethidium bromide treatment or suppression of critical components of the mtDNA maintenance machinery have shown impaired proliferation only when a critical level of mtDNA (less than 25% of initial content) is reached, which suggests that a minimal level of mtDNA is sufficient for cell proliferation (Jazayeri et al, 2003;Jeng et al, 2008). Interestingly, the effects of PNC1 on cell size and ROS production were not as tightly correlated with the degree of PNC1 suppression (Floyd et al, 2007 and this study).…”
Section: Pnc1 Regulates Mitochondrial Function and Emtmentioning
confidence: 99%
“…ATP also serves as an extracellular signaling molecule involved in vascular tone, synaptic transmission, and cell death (6,7). Cellular ATP levels have been reported to reflect cell viability, including cell survival, cell growth, and morphology (8,9). Furthermore, it has been reported that complete ATP depletion (Ͻ5% of control) results in necrosis, and partial ATP depletion (ϳ10 -65% of control) induces apoptosis, as evidenced by internucleosomal DNA cleavage, changes in cellular morphology, and alterations in the plasma membrane (10).…”
mentioning
confidence: 99%
“…미토콘드리아 DNA의 복제수(mitochondrial copy number, mtCN)는 저산소증과 호르몬 자극같은 미세 환경 들에 의해 변화된다 [28,29]. 활성산소와 같이 미토콘드 리아의 기능 장애를 일으키는 경우에서는 mtCN는 감소 하였으며 [30], 실험적으로 mtCN을 유지하는 것은 미토 콘드리아의 기능을 보존하고 세포성장에 필수적임을 증명하였다 [20]. 종양에서의 mtCN는 두경부암, 난소암 및 식도암에서는 증가하였고 [18][19][20].…”
Section: 재료 및 방법unclassified
“…활성산소와 같이 미토콘드 리아의 기능 장애를 일으키는 경우에서는 mtCN는 감소 하였으며 [30], 실험적으로 mtCN을 유지하는 것은 미토 콘드리아의 기능을 보존하고 세포성장에 필수적임을 증명하였다 [20]. 종양에서의 mtCN는 두경부암, 난소암 및 식도암에서는 증가하였고 [18][19][20]. 간세포암, 위암, 유 방암 및 신세포 암에서는 감소하였다 [21][22][23][24][25] …”
Section: 재료 및 방법unclassified